ABDUCTIVE IMAGE FORMATION - László GÁL; Gabriella GÁL (Studia Universitatis Babeș-Bolyai. Philosophia, 2018)
Our study, according to its title, will consist of four parts. Initially, we want to elucidate the concept of abduction and the characteristics of abductive reasoning. Then we will turn our attention to visual abduction, proceeding from its logical and psychological discussion in the literature. Finally, we will deal with the question whether building design proceeds abductively. If we will assume that it does, then we will argue for this point. Our argument will be based on a specific example, supplied by the design of an archaeological museum by Gál Gabriella. By way of a conclusion, we will present our logical and philosophical interpretations.